Heterotopic cervical pregnancy after in-vitro fertilization - case report and literature review - Terra, Maria Eduarda Furtado Fernandes (JBRA Assist Reprod, 2019)
Heterotopic cervical pregnancy is an uncommon condition, with a rising incidence due to the increasing number of pregnancies resulting from in-vitro fertilization (IVF). Although it is associated with maternal-fetal complications, there is no consensus in the literature about the best approach for this condition. This study aims to report a case of cervical heterotopic gestation after IVF in which the intrauterine pregnancy was preserved, with spontaneous elimination of the cervical gestational sac after patient sedation and introduction of the vaginal speculum. In addition, we reviewed the literature on the subject, which demonstrated that most cases have a favorable outcome, especially after treatment with surgical excision of the cervical pregnancy. The growing body of evidence is still scarce to define the best treatment for this condition.